Optimalisasi Dalam Memperlancar Pengiriman Peti Kemas Dengan Menggunakan Aplikasi mySPIL: Studi Kasus Pada PT. Salam Pasific Indonesia Lines TBK Surabaya : Agus Hadi Purwantomo, S. Sumardi, Rufiajid Navy Abritia*, Hilda Emeraldo Ahmad Ediarsa - Agus Hadi Purwantomo; Sumardi; Rufiajid; Hilda Emeraldo Ahmad Ediarsa (Nama Jurnal Akmi, 2020)
Shipping is one of the service industries that are developing at this time, where the business field is shipping goods. Shipping companies are currently using more containers or containers in their shipping services. The use of these containers is useful for storing more and easier goods and packaged goods that do not experience damage. This study seeks to examine how the concept of the application of mySPIL in container shipments. This research refers to the application of mySPIL which is the first container shipping application in Indonesia capable of providing timeliness in the issuance of documents for container shipments need to be optimized through this application, it needs to be assessed using a qualitative method and descriptive data analysis technique samples taken at PT SPIL. Obtained the following research results: The implementation of containerized shipments using the mySPIL application makes it easy for service users or goods owners (shipper) to carry out container shipments. In addition to convenience, it can also save time and money, in addition encountered various obstacles which are the drawbacks of this application, among others, the mySPIL application can only be used for ordering, the need to adjust the offline method to an online method, as well as the lack of promotions or advertisements conducted by PT Salam Pasific Indonesia Line Tbk. about the mySPIL application.